Excess Fibrin Deposits Decrease Fetal Weight of Pregnant Mice Infected by Plasmodium berghei - Andari, Desy; Rahma, Zainabur; yuliyanik, Yuliyanik; Sasmito, Sujarot Dwi; Mintaroem, Karyono; Fitri, Loeki Enggar (Journal of Tropical Life Science, 2014)
Low birth weight is commonly attributed to malaria in pregnancy, but the cellular and molecular mechanisms that underlie this poor birth outcome are incompletely understood. A universally described histopathological feature of placental malaria is excessive deposition of fibrin, the end-product of the coagulation cascade. This study was conducted to compare fibrin deposit in pregnant mice that infected by Plasmodium berghei (treatment group) to the normal pregnant mice (control group) and its association with fetal weight. This research is in vivo experimental laboratory study that used 18 pregnant Balb/c mice which divided to the control the group (8 mice) and treatment group (9 mice infected by P.berghei). Placentas were staining with Haematoxylin-Eosin (HE) for fibrin deposits examination whereas fetal weight was performed with Mettler analytical balance AE 50. Fetal weight of the treatment group was lower than those of the control group (t test, p=0,002). Fibrin deposits were increased in the treatment group (t test, p=0,005) and influenced weight of fetuses (Spearman r=-0,586, p=0,014). Weights of fetuses are interfered by fibrin deposits during malaria infection.